Keterampilan Komunikasi Verbal Calon Guru Biologi Melalui Pembelajaran Jarak Jauh: Oral Communication Skills of Prospective Biology Teachers Through Distance Learning - Idah Hamidah; Lesy Luzyawati (BIODIK, 2022)
One of the communication skills that must be possessed by prospective biology teachers is oral communication skills. Communication learning plays an important role. The aim of this research is to know the oral communication skills of prospective biology teachers through distance learning. This study uses True Experimental Design with a type of one shoot case study design. A research sample of 30 students of Wiralodra University Biology Education was randomly selected. The results of the data analysis showed that the communication skills of prospective biology teachers in distance learning using the Moodle platform were in the good category with a percentage of 81.8%. Key words: Communication Skills, Prospecive Biology Teacher Â  Abstrak. Salah satu keterampilan komunikasi yang harus dimiliki oleh calon guru biologi yaitu keterampilan komunikasi lisan. Dalam pembelajaran komunikasi berperan penting. Tujuan penelitian ini adalah untuk mengetahui keterampilan komunikasi lisan calon guru biologi melalui pembelajaran jarak jauh. Penelitian ini menggunakan True Experimental Design dengan jenis rancangan one shoot case study. Sampel penelitian sebanyak 30 mahasiswa Pendidikan Biologi Universitas Wiralodra yang dipiih secara random. Hasil analisis data menunjukkan bahwa Keterampilan komunikasi mahasiswa calon guru biologi pada pembelajaran jarak jauh dengan menggunakan platform Moodle berada pada kategori baik dengan presentase sebesar 81,8%. Kata kunci: Komunikasi Lisan, Calon Guru Biologi